(untitled) (Research, Society and Development, 2021)
The objective of this work was to evaluate the effect of the presence and absence of indolebutyric acid and concentrations of humic substances on the in vitro rooting of ’Woodard’ blueberry. The experimental design was completely randomized, in a 2x3 bifactorial scheme, with the following factors: presence (1 mg L-1) or absence (0 mg L-1) of indolebutyric acid (IBA) growth regulator and humic substances concentrations (SH) (Solohumics®) (0; 1; 2; 3 mg L-1). At 60 days it was evaluated: survival percentage, shoot length, number of shoots, length of the largest shoot, percentage of rooting, number of roots, length of the largest root, fresh and dry matter weight of shoot and root. The results show that, with the exception of the treatment without the use of SH and AIB, in the others there was 100% survival. The longest shoot length was verified without the use of IBA and with 3 mg L-1 of SH, as well as the largest shoot, root, number of roots, shoot fresh matter mass and dry matter mass of the shoots. roots. The greatest number of shoots was observed without the use of IBA and with 2 mg L-1 of SH. As for rooting, without the use of AIB and SH there was no root formation, differing from the others, which showed 100% rooting. The highest average of shoot dry matter mass was obtained with the use of IBA and 3 mg L-1 of SH. Thus, it was concluded that the in vitro rooting of ’Woodard’ blueberry can be performed using 3 mg L-1 of humic substances, without indolebutyric acid.